Purification and properties of pectinesterase from papaya - Lourenco, Euclides J. [UNESP]; Catutani, Adelaide T. [UNESP] (Wiley, 1984)
Pectinesterase (PE) was partially purified from papaya pulp, and its biochemical properties were studied. The enzyme was eluted in a single peak after DEAE‐cellulose and Sephadex G‐100 chromatography. The PE had a molecular weight of 53000 and showed an optimum pH of 8.0. Its activity was dependent on an NaCl concentration of 0.2M. The enzyme was heat stable: approximately 80% of the original activity remained after 60 min of heating at 50°C but completely inactivated by incubation at 80°C for 1 min. The activity was linear with time and protein concentration. The maximum reaction in 3 min was found at 60°C and the initial rate increased 9‐fold from 20 to 60°C. The estimated Km was 0.12g litre−1 with citrus pectin as the substrate. The kinetic study revealed that polygalactur‐onic acid is a competitive inhibitor, and a Ki value of 0.07 g litre−1 was determined. On the basis of this study, papaya PE properties resembled those of pectinesterase from other sources. Copyright © 1984 John Wiley & Sons, Ltd
Keywords: biochemical properties; Carica papaya; enzyme purification; pectinesterase